Pendidikan Madrasah Berbasis 4.0 dalam Bingkai Manajemen Mutu - Bahri, Samsul (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2019)
This paper examines 4.0-based madrasa education in a quality management frame with descriptive historical methods. This study discusses the world of madrasa education has many opinions, therefore, the application of the 4.0-based quality management system in improving quality to produce products that have cognitive and affective, psychomotor intelligence and maintain schools with distinctive characteristics of character and noble identity based on values religious values and being able to self-regulate in the 4.0 era. not maximal, it requires government policy by providing sufficient budget, so that madrasas can support their teachers, complete their educational facilities and infrastructure, provide digital-based textbooks, God willing, which can be easily resolved. The National Education System Law, which was passed several years ago, would provide an opportunity for the government to give adequate attention to all educational institutions, including madrasa education.